Technology Entrepreneurship Project (ENT 600) : TurboTex.Co / Aina Yasmin Farhan Mior Karim - Mior Karim, Aina Yasmin Farhan; Ridzuan, Mohammad Syafirul Nazreen; Hamadan @ Hamdan, Muhammad Syahiir; RAHMAT, Nur ‘Aliah ‘Aqilah; Ahmad Redzuan, Nur Faatihah (2021)
The TurboTex.Co is a company that produce the technology product which is Bombastic blender known as kitchen appliances. Nowadays, people are looking for the new or advance product with current technology as it is become one of the development. Therefore our company come out with the product that can solve the problem of consumer. The Bombastic blender is offer with a concept of flexible and compactable that suitable for all range of consumer. This is because, our blender will provide with two type of the containers such as collapsible and thermal container which can directly use after blending. This product has create with the new innovation standard with the needs and requirement of the customers. The bombastic blender is offer with high quality at reasonable price that can help to growth the product in market. Next, the target market is more focus on wide range of people especially for sports person and housewives. It can also be used for the travel purpose because easy to bring it everywhere since our product is travel-friendly and easy to use. Therefore, the products are is make to provide convenience to consumers. As a projections our product has been innovate which is multi-use blender by providing two type of containers and blades. The advantage of this product it can attract many customers with new technology apply to Bombastic blender. Therefore it will be able to compete well at the target market. This is because, people want the product that give benefit to them. Even there are many type of blender exist among well-known branded but with our uniqueness of the Bombastic blender it can help to stand in the market. In addition, the profitability of our company is estimated to be increase in year 2 around 10% and 15% in the year 3. With the consistency of the product's value it will help to gain the profit to the company. In our company there have people who are responsible to manage all stuff of the company. Thus, TurboTex.Co is consist of management team such as General Manager, Marketing Manager, Administrative Manager, Financial Manager and Operation Manager. They will play an important positions in the organization to run the business of company.